LANGUAGE ANXIETY IN YOUNG LEARNERS: HOW TO CREATE A SUPPORTIVE LEARNING ENVIRONMENT - Djalolov, Furqat (Journal of Higher Education and Academic Advancement, 2025)
Objective: This study investigates the impact of language anxiety on young learners and aims to identify pedagogical strategies that effectively mitigate anxiety in early foreign language education. Method: Employing a mixed-methods approach, the research combines classroom observations, teacher interviews, and standardized anxiety scale assessments to examine emotional and instructional dynamics in language learning environments. Results: Findings reveal that 65% of young learners experience moderate to high anxiety, especially during oral tasks. However, classrooms characterized by empathetic teaching practices, collaborative peer interactions, consistent positive reinforcement, and error-tolerant feedback significantly reduced anxiety levels and enhanced learner participation and language performance. Novelty: Unlike existing literature that predominantly focuses on adult learners, this study provides a comprehensive analysis of anxiety-specific pedagogical interventions tailored to the cognitive and emotional needs of children. The research emphasizes the integration of emotionally responsive teaching strategies as a means to lower affective filters and foster linguistic competence in young learners. The findings advocate for a shift in early language instruction toward child-centered, emotionally supportive methodologies to promote sustainable language acquisition outcomes.